Effects of tropical high tannin non legume and low tannin legume browse mixtures on fermentation parameters and methanogenesis using gas production technique - Seresinhe, T (Asian-Australasian journal of animal sciences, 2012)
In vitro experiments were conducted to evaluate the suitability of several mixtures of high tanniniferous non legumes with low tanniniferous legumes on in vitro gas production (IVGP), dry matter degradation, Ammonia-N, methane production and microbial population. Eight treatments were examined in a randomized complete block design using four non-legumes and two legumes (Carallia integerrima×Leucaena leucocephala (LL) (Trt 1), C. integerrima×Gliricidia sepium (GS) (Trt 2), Aporosa lindeliyana×LL (Trt 3), A. lindeliyana×GS (Trt 4), Ceiba perntandra×LL (Trt 5), C. perntandra×GS (Trt 6), Artocarpus heterophyllus×LL (Trt 7), A. heterophyllus×GS (Trt 8). The condensed tannin (CT) content of non legumes ranged from 6.2% (Carallia integerrima) to 4.9% (Ceiba perntandra) while the CT of legumes were 1.58% (Leucaena leucocephala) and 0.78% (Gliricidia sepium). Forage mixtures contained more than 14% of crude protein (CP) while the CT content ranged from 2.8% to 4.0% respectively. Differences (p<0.05) were observed in in vitro gas production (IGVP) within treatments over a 48 h period dominated by C. perntandra×G. sepium (Trt 6). The net gas production (p<0.05) was also high with Trt6 followed by A. heterophyllus×L. leucocephala (Trt 7) and A. heterophyllus×G. sepium (Trt 8). Highest (p>0.05) NH3-N (ml/200 mg DM) production was observed with the A. heterophyllus×G. sepium (Trt 8) mixture which may be attributed with it's highest CP content. The correlation between IVGP and CT was 0.675 while IVGP and CP was 0.610. In vitro dry matter degradation (IVDMD) was highest in Trt 8 as well. Methane production ranged from 2.57 to 4.79 (ml/200 mg DM) to be synonimous with IVGP. A higher bacteria population (p<0.05) was found in C. perntandra×G. sepium (Trt 6) followed by Artocarpus heterophyllus+G. sepium (Trt 8) and the same trend was observed with the protozoa population as well. The results show that supplementing high tannin non leguminous forages by incremental substitution of legume forage increased gas production parameters, NH3-N, IVDMD and microbial population in the fermentation liquid. Methane production was not significantly affected by the presence of CT or different levels of CP in forage mixtures. Among non legumes, Ceiba perntandra and Artocarpus heterophyllus performed better in mixture with L. leucocephala and G. sepium